ANALISA SISTEM PENGAMAN GENERATOR PLTDG DI PT INDONESIA POWER UNIT PEMBANGKITAN BALI - Putu Wira Asta Dharma; Cok Gede Indra Partha; Ngakan Putu Satriya Utama (Program Studi Teknik Elektro UNUD, 2018)
The need for electrical power, especially in Bali, is increasing every year. Therefore, the Bali’s Generating Unit of PT Indonesia Power has replaced the Diesel-powered Electrical Generator Pembangkit Listrik Tenaga Diesel (PLTD) with ‘the Gas-powered Diesel of Electrical Generator Pembangkit Listrik Tenaga Diesel Gas’ (PLTG). Such a replacement causes the change in the generating capacity power which affects the setting and system of protection. This current study was intended to analyze the relay protecting system using the short connecting simulation method in the ETAP program in order to be able to identify the maximum and minimum disturbing current, the working time setting and the OCR (Over Current Relay) and GFR (Ground Fault Relay) protecting coordination. Based on the result of simulation and calculation, it can be concluded that the OCR took 1.18 seconds to work, faster than the GFR, which took 2.25 seconds to work.